CORRECTION OF DEFORMITIES FOLLOWING DEEP BURNS ON EXTENSOR SURFACE OF THE HAND - C. P. SAWHNEY (Indian Journal of Plastic Surgery)
Postburn contractures on the extensor aspect of hand produce crippling deformities. The deformities produced vary from extension contractures with or without associated web contractures, scar syndactyly, non-healing ulcers, disrupted extensor mechanism, contractures of musculotendinous units and capsular ligaments. Stiffness and/or subluxations of joints further complicates the problems. Release of contracture, skin grafting, judicious splintage and physiotherapy has been the sheet-anchor of treatment. With this regime it has been possible to restore near normal function in majority of the cases at our centre.